Balancing Act: Managing Disruptive Behaviors in Elementary Classrooms through Qualitative Research - Putri Wulanjari; Teguh Supriyanto; Tri Murtini (Jurnal Ilmu Pendidikan, 2024)
Disruptive behavior of students in elementary schools should get serious attention because it will have an impact on the effectiveness of learning. This study aims to describe students' disruptive behavior in the learning process and teachers' strategies for overcoming students' disruptive behavior. The supporting informants of this research are teachers and students of class VI SD Negeri Wates 02. This type of research uses qualitative research with a descriptive qualitative approach. This research data was collected through observation, interviews, documentation, and questionnaires. Analysis of research data begins with the stages of data collection, data reduction, data presentation, and conclusions. Data validity is checked using the trust test and objectivity test. Indicators to be examined on student disruptive behavior include forms, factors, differences, and teacher strategies. The results of research from observations and interviews show that there are still students who carry out disruptive behavior. The causative factors are school environmental factors, genetic or biological factors, community environmental factors, and family factors, in various ways, the teacher carries out strategies to overcome the behavior carried out by students with several methods, namely classroom management methods, behavior management methods and finally social skills methods with this deterrent students and disruptive behavior carried out by students is reduced.